(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: In this research, the Authors examined the patterns of cybercrime perpetration and victimization in three countries (Hungary, Finland, and the United States). Methodology: The online questionnaire developed by the research team was taken in April 2020 in the three countries, with the help of the Qualtrics questionnaire system, on a representative sample. The data were analyzed using the SPSS program package. Chi-square test and Fisher test were used to analyze the frequencies, and Mann–Whitney test was used to compare the mean values. Regression models were set up for each type of victimization (Binary Logistic Regression). Findings: The results of the research show that in the case of the United States, which is far ahead in the prevalence of the use of technical devices, the number of online crimes and victims is significantly higher than in the two European countries. In all three countries, men reported higher levels of online activity and more frequent victimization compared to women. In the case of many delicts, the lowest indicators can be found in our country, showing similar trends to the Finnish results. Authors also found a significant difference in the frequency of victimization by country. In the Hungarian sample, a higher frequency of online victimization can be observed compared to offline acts. The study examines the appropriateness of some traditional explanatory theories, among which the control theories and the routine activity theory offer an explanation on this new special crime surface. Value: The research examines and compares the characteristics of certain forms of crime in a new, under-explored area with similar types of offline offences, seeking explanations and thus offering an opportunity to develop a strategy for the prevention of new types of crime.